2016
DOI: 10.1186/s13058-016-0728-y
|View full text |Cite|
|
Sign up to set email alerts
|

Genome co-amplification upregulates a mitotic gene network activity that predicts outcome and response to mitotic protein inhibitors in breast cancer

Abstract: BackgroundHigh mitotic activity is associated with the genesis and progression of many cancers. Small molecule inhibitors of mitotic apparatus proteins are now being developed and evaluated clinically as anticancer agents. With clinical trials of several of these experimental compounds underway, it is important to understand the molecular mechanisms that determine high mitotic activity, identify tumor subtypes that carry molecular aberrations that confer high mitotic activity, and to develop molecular markers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 43 publications
2
24
0
Order By: Relevance
“…KIF4A, among all six KIFs selected in our study, is the only one that functionally involved in multi-stages of mitosis, participating in chromosome condensation, anaphase spindle mid-zone formation and cytokinesis [50,62,68]. Given the hyperactive proliferation of tumor cells, overexpression of the six KIFs selected as expected, which in accordance with the results given in our study, and further demonstrations were found on both cellular and molecular levels reported in previous studies [69][70][71][72]. Tumorigenic functions of KIFs affect various aspects of breast cancer, including metastasis, progression and chemotherapy resistance.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…KIF4A, among all six KIFs selected in our study, is the only one that functionally involved in multi-stages of mitosis, participating in chromosome condensation, anaphase spindle mid-zone formation and cytokinesis [50,62,68]. Given the hyperactive proliferation of tumor cells, overexpression of the six KIFs selected as expected, which in accordance with the results given in our study, and further demonstrations were found on both cellular and molecular levels reported in previous studies [69][70][71][72]. Tumorigenic functions of KIFs affect various aspects of breast cancer, including metastasis, progression and chemotherapy resistance.…”
Section: Discussionsupporting
confidence: 93%
“…Tumorigenic functions of KIFs affect various aspects of breast cancer, including metastasis, progression and chemotherapy resistance. Silencing of KIF10 and KIF18A were both reported inhibitions to the proliferation of breast cancer cells via deregulating cell division [20,69]. Lysosomal stability was demonstrated to enhance the survival of breast cancer cells while the knocking down of KIF20A conduced the permeabilization of the lysosomal membrane, which in turn, causing cellular death [73].…”
Section: Discussionmentioning
confidence: 99%
“…Identification of tumor addictions (dependence on a gene for proliferation and survival) has in the past led to the development of novel therapies, notably the discovery of ERBB2 amplification and overexpression, now targeted by a number of therapies in breast cancer 3 . Despite progress in characterizing the genomic landscape of breast cancer 4 , 5 and TNBC specifically 2 , 6 8 , targetable biological dependencies remain elusive and poorly characterized. With the exception of clonally dominant mutations in TP53 , TNBCs demonstrate a high degree of inter-tumor and intra-tumor heterogeneity at the mutational level with each driver mutation only present in a subset of tumors and clones within any individual tumor 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Genes that are found in amplified regions and are highly expressed, may be drivers of important “hallmarks” of malignancy 11 and potentially represent essential tumor addictions. A number of high-throughput loss of function screening studies have identified gene addictions in cellular models of cancer including breast cancer models 4 , 5 , 12 but functional validation has been limited and studies have rarely been informed by evidence of upregulation of gene copy number or mRNA in large numbers of patient tumors. Therefore, the main aim of this study is to identify and validate recurrently amplified genes as being important for malignant phenotypes in TNBC.…”
Section: Introductionmentioning
confidence: 99%
“…He stated that it is necessary to make links between functional oncogene signatures of cancer subsets and combinations of drugs that can be used to guide the treatment of individual patients to improved outcomes and decreased toxicity [17] . Joe Gray gave an example of large-scale drug screening by defining a molecular signature, which may guide therapeutic approaches for tumors with high mitotic network activity [18] . This approach is supported by Seashore-Ludlow et al [19] who developed a novel annotated cluster multidimensional enrichment analysis to explore the association between groups of small molecules and groups of cancer cell lines in a new, quantitative, sensitive data set.…”
Section: Targeted Therapymentioning
confidence: 99%